Evaluación de técnicas de barrera en queso fresco como reductores del deterioro en refrigeración - Marcillo Cevallos, Helen Melina (2021)
The purpose of this research was to evaluate the different barrier techniques according to the physicochemical and microbiological properties in the fresh cheese in order to reduce the deterioration in refrigeration. A DCA (Randomized Complete Design) of a factor with an intervening variable was used. Factor: Barrier techniques (glass container, plastic tray, black plastic sleeves, plastic sleeve with zipper and a control); Intervening variable: Time (0 days, 3 days, 6 days, 12 days), consisted of five treatments with three repetitions each one and four periods of measurement being the time an intervening variable, each experimental unit was of 450 g of cheese giving a total of 27 kg of cheese with a total of 60 experimental units. The variables were in function to reduce the deterioration in refrigeration based on the indicators of the fresh cheese: physical-chemical (color, pH, humidity and oxidation); microbiological (Escherichia Coli, Staphylococcus aureus).